Pengaruh Kemampuan Inteligensi dan Task Commitment Terhadap Prestasi Belajar Matematika - Febryanti Febryanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This study is based on the number of children who actually have the potential to achieve high learning, but it has low achievement, because some factors that do not have, such as task commitment. This study aims to determine how the influence of intelligence and task commitment to the achievement of learning mathematics students SMPN 4 Sendana. This research type is correlation research. The population in this study is the students of class VIII SMP Negeri 4 alone. Sampling technique used